2015
DOI: 10.4293/jsls.2015.00067
|View full text |Cite
|
Sign up to set email alerts
|

Low-Friction Minilaparoscopy Outperforms Regular 5-mm and 3-mm Instruments for Precise Tasks

Abstract: Background and Objectives:Therapeutic laparoscopy was incorporated into surgical practice more than 25 y ago. Several modifications have since been developed to further minimize surgical trauma and improve results. Minilaparoscopy, performed with 2- to 3-mm instruments was introduced in the mid 1990s but failed to attain mainstream use, mostly because of the limitations of the early devices. Buoyed by a renewed interest, new generations of mini instruments are being developed with improved functionality and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…21 Compared with conventional laparoscopy, minilaparoscopy has the advantages of causing less trauma to the abdominal wall and, consequently, less postoperative pain, requiring shorter hospital stay, providing better visualization of the surgical field, and enabling more precise movements. Firme et al 22 showed that for gross grasping tasks, the conventional 5-mm instruments are better, but for more precise and complex movements, the low-friction 3-mm instruments performed best. These conclusions lead to the possibility of preserving more splenic tissue, particularly in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…21 Compared with conventional laparoscopy, minilaparoscopy has the advantages of causing less trauma to the abdominal wall and, consequently, less postoperative pain, requiring shorter hospital stay, providing better visualization of the surgical field, and enabling more precise movements. Firme et al 22 showed that for gross grasping tasks, the conventional 5-mm instruments are better, but for more precise and complex movements, the low-friction 3-mm instruments performed best. These conclusions lead to the possibility of preserving more splenic tissue, particularly in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…Trocar dislocation and skin reinsertions were significantly diminished, consequently reducing abdominal trauma, resulting in less pain and improved aesthetics. 1 , 7 , 9 , 10 , 18 21 ( Figure 3 ) This technique of mini-TEP without mesh fixation also entails a considerable reduction in cost, because it does not use expensive meshes, disposable instruments, the fragile 3-mm laparoscope, sutures, glue, or tackers, and hence it is possible to perform this type of repair on a larger number of patients to their advantage. 1 , 7 , 8 , 10 …”
Section: Discussionmentioning
confidence: 99%
“…An important feature of minilaparoscopic surgery, the decreased surgical trauma is achieved by the reduction in diameter of the laparoscopic instruments and trocars. 18 – 20 This improvement is obtained with the maintenance of range of motion in triangulation throughout surgery. Along with the benefit of low-friction trocars, minilaparoscopy has the potential of improving ergonomics and, therefore, provides the surgeon the precision that is needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations